INFLUENCE OF FOLIAR NUTRITION ON DRY MATTER PRODUCTION AND NUTRIENT UPTAKE OF RAINFED Bt. COTTON (Gossypium hirsutum L.) - T. RAM PRAKASH, R. SRIKANTH, A.SRINIVAS, K.AVIL KUMAR and (The Journal of Research, PJTSAU, 2019)
Cotton (Gossypium hirsutum L.) is maintaining its unique name and fame as the ‘King of Fibres’ and ‘White Gold’ because of its higher economic value among cultivable crops for quite a long period. The rainfed cotton when grown on red soils yield levels are low due to poor agronomic practices, especially ferti lization. Nutrient management in cotton is again a complex phenomenon due to simultaneous production of its vegetative and reproductive parts during the active growth stage. Cotton needs the highest quantity of nutrients at squaring, blooming and boll development. Augmentation of nutrient supply through foliar application at such critical stages may increase yield (Bhatt and Nathu, 1986). Cotton mainly grown as the rainfed crop and occurrence of dry spells and water logging situations are common due to vagaries of monsoons. Under such situations foliar application is recommended instead of soil application. The advantages of foliar feeding are quick plant response, small quantity of nutrient, compensation for the lack of soil fixation, avoiding root uptake problems, increased yield and fibre quality in cotton.